Bits and pieces: A survey characterizing equipment use on the heads of therapeutic/adaptive riding horses in the United States - Sarah Jean Reega; Sarah K. Matlock; Sharon Butler; Kathleen R. Auchmoody; Ann M. Hess; B. Caitlin Peters (Journal of Veterinary Behavior, 2026)

Automated 24-h cattle feeding behaviour analysis using Raspberry Pi, infrared imaging, and deep learning-based head position and ID classification - G. Wager-Jones; M. Butler; W.E. Harris; M. Rutter; E. Bleach; K. Behrendt (Biosystems Engineering, 2026)

Horizon scanning to identify priority research questions for the South African marine shore-based recreational fishery - K Hewett; CS Bova; EC Butler; A-R Childs; MW Farthing; BQ Mann; JB Mann-Lang; AC Winkler; K Hyder; WM Potts (African Journal of Marine Science, 2025)

Genetic control of stem elongation in common bean and the influence of age and flowering time - Chantelle J. Beagley; Jacqueline K. Vander Schoor; Jakob B. Butler; James L. Weller (Theoretical and Applied Genetics, 2025)
Key message Genetic analysis of stem elongation in common bean identified loci acting at different developmental stages and reveals interactions with flowering time. Abstract Stem internode elongation is a major determinant of growth habit and plant height, and is often responsive to environmental signals, making it an integral component of plant architecture and a core characteristic targeted for crop improvement. More effective exploitation of stem elongation requires increased understanding of not only major determinants, but also of more subtle, specific influences as breeders seek to further refine adaptation to local growing environments. Common bean is a globally important legume crop and exhibits extensive variation in stem elongation, but there is little knowledge about the underlying genetic control. To better understand this trait, we performed a comprehensive genetic analysis in a wide F 2 cross between wild and domesticated bean. By conducting quantitative trait locus (QTL) analyses of the length of individual internodes, we discovered four main genomic regions influencing internode length at different stages of development. Of these, one demonstrated strong association with the two known flowering genes Fin and Ppd on chromosome 1, while two other regions were validated in subsequent F 3 and F 4 generations and were demonstrated to be independent of flowering time. These results highlight the complex dynamic nature and potential pleiotropic interactions of elongation genes throughout development, and indicate new avenues of inquiry towards improving crop adaptation to specific environments.

Performance of summary measures of core body temperature in heat-related health outcome regression models - M. Dally; A. Dye-Robinson; Y. Li; D. Jaramillo; K. Villarreal-Hernandez; L. Krisher; J. Butler-Dawson; J. Schaeffer; J. L. Adgate; K. A. James; L. S. Newman (International Journal of Biometeorology, 2025)

Conservation of an isolated and genetically unique population: red squirrels on the Isle of Wight - Alyson E.V. Buchanan; Demetra Andreou; Kathy H. Hodder; Melissa A. Toups; Phillipa K. Gillingham; Marin Cvitanović; Helen Butler; Emilie A. Hardouin (Biodiversity and Conservation, 2025)
Island populations face a higher extinction risk than mainland ones due to their smaller population sizes, limited genetic diversity, and increased vulnerability to environmental changes and stochastic events. The Isle of Wight red squirrel population is culturally and economically significant, being the largest remaining population in Southern England and genetically distinct from European populations. We used a multidisciplinary approach to assess the population’s long-term viability, evaluating habitat and food resources, analysing microsatellite genetic data, and using life history data to model population viability. Results indicated that natural food resources, supplemented by additional feeding, could sustain and support population growth. Microsatellite data identified two genetic clusters in the east and west of the island. Although F ST values were non-significant, indicating gene flow between subpopulations, elevated F IS values suggest localised mating dynamics driven by limited dispersal and spatial structure rather than systemic inbreeding. Population viability analyses suggested that habitat fragmentation and localised inbreeding do not pose immediate threats. However, maintaining connectivity between subpopulations remains crucial to preserving genetic diversity and reducing future risks of genetic isolation or increased inbreeding. Under pessimistic scenarios with reduced survival rates and fewer litters, model predictions indicated population decline and increased extinction risks. Future research should incorporate fine-scale spatial genetic analyses using genome data to explore population structure, local adaptation, and differentiate local mating dynamics from population-wide inbreeding. While direct data on inbreeding, litter sizes, and survival rates are challenging to obtain, these insights are critical for understanding population dynamics and guiding conservation efforts.

Unmet needs among long-term breast cancer survivors - Rina A. Yarosh; Hazel B. Nichols; Rachel Hirschey; Erin E. Kent; Deborah K. Mayer; Melissa A. Troester; Eboneé N. Butler (Cancer Causes & Control, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Fatty acid production and associated gene pathways are altered by increased salinity and dimethyl sulfoxide treatments during cryopreservation of Symbiodinium pilosum (Symbiodiniaceae) - Joseph K. Kihika; John K. Pearman; Susanna A. Wood; Lesley L. Rhodes; Kirsty F. Smith; Matthew R. Miller; Juliette Butler; Ken G. Ryan (Cryobiology, 2024)

Assessing pore network heterogeneity across multiple scales to inform CO2 injection models - Shane K. Butler; César Barajas-Olalde; Xue Yu; Matthew E. Burton-Kelly; Blaise A.F. Mibeck; Lingyun Kong; Bethany A. Kurz; Dustin Crandall (International Journal of Greenhouse Gas Control, 2023)

Accounting for herbaceous communities in process‐based models will advance our understanding of “grassy” ecosystems - Kevin R. Wilcox; Anping Chen; Meghan L. Avolio; Ethan E. Butler; Scott Collins; Rosie Fisher; Trevor Keenan; Nancy Y. Kiang; Alan K. Knapp; Sally E. Koerner; Lara Kueppers; Guopeng Liang; et al. (Global Change Biology, 2023)
Grassland and other herbaceous communities cover significant portions of Earth's terrestrial surface and provide many critical services, such as carbon sequestration, wildlife habitat, and food production. Forecasts of global change impacts on these services will require predictive tools, such as process‐based dynamic vegetation models. Yet, model representation of herbaceous communities and ecosystems lags substantially behind that of tree communities and forests. The limited representation of herbaceous communities within models arises from two important knowledge gaps: first, our empirical understanding of the principles governing herbaceous vegetation dynamics is either incomplete or does not provide mechanistic information necessary to drive herbaceous community processes with models; second, current model structure and parameterization of grass and other herbaceous plant functional types limits the ability of models to predict outcomes of competition and growth for herbaceous vegetation. In this review, we provide direction for addressing these gaps by: (1) presenting a brief history of how vegetation dynamics have been developed and incorporated into earth system models, (2) reporting on a model simulation activity to evaluate current model capability to represent herbaceous vegetation dynamics and ecosystem function, and (3) detailing several ecological properties and phenomena that should be a focus for both empiricists and modelers to improve representation of herbaceous vegetation in models. Together, empiricists and modelers can improve representation of herbaceous ecosystem processes within models. In so doing, we will greatly enhance our ability to forecast future states of the earth system, which is of high importance given the rapid rate of environmental change on our planet.

Air pollution and the sequelae of COVID-19 patients: A multistate analysis - Michael Jerrett; Claudia L. Nau; Deborah R. Young; Rebecca K. Butler; Christina M. Batteate; Ariadna Padilla; Sara Y. Tartof; Jason Su; Richard T. Burnett; Michael J. Kleeman (Environmental Research, 2023)

Feasibility and Tolerability of Daily Microgreen Consumption in Healthy Middle-Aged/Older Adults: A Randomized Crossover Trial - S. Holmes; K. Michell; M. Butler; B. Smith; A. Vazquez; E. Woolf; L. Grabos; S. Lee; S. Newman; M. Uchanski; T. Weir; S. Johnson (Journal of the Academy of Nutrition and Dietetics, 2023)

Effects and significance of groundwater for vegetation: A systematic review - K. Glanville; F. Sheldon; D. Butler; S. Capon (Science of The Total Environment, 2023)

Patterns of genomic diversity and linkage disequilibrium across the disjunct range of the Australian forest tree Eucalyptus globulus - Jakob B. Butler; Jules S. Freeman; Brad M. Potts; René E. Vaillancourt; Hossein V. Kahrood; Peter K. Ades; Philippe Rigault; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2022)
The evolutionary trajectory of a population both influences and is influenced by characteristics of its genome. A disjunct population, for example is likely to exhibit genomic features distinct from those of continuous populations, reflecting its specific evolutionary history and influencing future recombination outcomes. We examined genetic diversity, population differentiation and linkage disequilibrium (LD) across the highly disjunct native range of the Australian forest tree Eucalyptus globulus , using 203,337 SNPs genotyped in 136 trees spanning seven races. We found support for four broad genetic groups, with moderate F ST , high allelic diversity and genome-wide LD decaying to an r 2 of 0.2 within 4 kb on average. These results are broadly similar to those reported previously in Eucalyptus species and support the ‘ring’ model of migration proposed for E. globulus . However, two of the races (Otways and South-eastern Tasmania) exhibited a much slower decay of LD with physical distance than the others and were also the most differentiated and least diverse, which may reflect the effects of selective sweeps and/or genetic bottlenecks experienced in their evolutionary history. We also show that F ST and rates of LD vary within and between chromosomes across all races, suggestive of recombination outcomes influenced by genomic features, hybridization or selection. The results obtained from studying this species serve to illustrate the genomic effects of population disjunction and further contribute to the characterisation of genomes of woody genera.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Seasonal, lunar, and diel patterns in spawning by the giant barrel sponge, Xestospongia muta - K. L. Neely; C. B. Butler (Coral Reefs, 2020)

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Impact of Climate Change and Land Use on Groundwater Salinization in Southern Bangladesh—Implications for Other Asian Deltas - M. A. Islam; M. A. Hoque; K. M. Ahmed; A. P. Butler (Environmental Management, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

The hidden hand is perceived closer to midline - Hassan G. Qureshi; Annie A. Butler; Graham K. Kerr; Simon C. Gandevia; Martin E. Héroux (Experimental Brain Research, 2019)

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Immune challenges decrease biliverdin concentration in the spleen of northern Bobwhite quail, Colinus virginianus - Melissa P. Homsher; Michael T. Astor; Justin K. Hines; Michael W. Butler (Journal of Comparative Physiology B, 2018)

Vulnerability of forests of the Midwest and Northeast United States to climate change - Chris Swanston; Leslie A. Brandt; Maria K. Janowiak; Stephen D. Handler; Patricia Butler-Leopold; Louis Iverson; Frank R. Thompson III; Todd A. Ontl; P. Danielle Shannon (Climatic Change, 2018)

Adaptation pathways: ecoregion and land ownership influences on climate adaptation decision-making in forest management - Todd A. Ontl; Chris Swanston; Leslie A. Brandt; Patricia R. Butler; Anthony W. D’Amato; Stephen D. Handler; Maria K. Janowiak; P. Danielle Shannon (Climatic Change, 2018)

Last Glacial pollen–climate reconstructions from Northland, New Zealand - R.M. Newnham; B. V. Alloway; K.A. Holt; K. Butler; A.B.H. Rees; J.M. Wilmshurst; G. Dunbar; I. Hajdas (Journal of Quaternary Science, 2017)
Despite wide‐ranging interest in the vegetation and climate of Northland, New Zealand, during the last glacial cycle, the region and timeframe lack quantitative climate reconstructions while land‐based pollen records have tended to be poorly dated and fragmentary. The region is also important for geochronology due to the co‐occurrence of the Rotoehu tephra, a widely dispersed isochron near the current limits of radiocarbon dating, and extensive subfossil wood remains of Agathis australis , with strong dendrochronological and dendroclimatological potential. We present new pollen records and temperature reconstructions from three sites set in coastal dune belts from western mid‐Northland (∼35°S), all containing Rotoehu tephra, that collectively span the last 70 ka. The phases and amplitude of temperature changes broadly align with those reported from elsewhere in New Zealand and with marine isotope climate–stratigraphic records, including maximum temperature depression of 6–8 °C during the last glacial maximum. We argue that these climatic patterns are intimately linked to shifts in the southern westerly wind belt, the northern margins of which extend to the region today. Correspondence between the Northland temperature shifts and atmospheric CO 2 supports the model of ocean–atmosphere CO 2 flux modulated by latitudinal migration of the southern westerlies. Copyright © 2017 John Wiley & Sons, Ltd.

Biophysical connectivity explains population genetic structure in a highly dispersive marine species - Nathan K. Truelove; Andrew S. Kough; Donald C. Behringer; Claire B. Paris; Stephen J. Box; Richard F. Preziosi; Mark J. Butler (Coral Reefs, 2017)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Short-interval cortical inhibition and intracortical facilitation during submaximal voluntary contractions changes with fatigue - Sandra K. Hunter; Chris J. McNeil; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2016)

Drinking water vulnerability to climate change and alternatives for adaptation in coastal South and South East Asia - M. A. Hoque; P. F. D. Scheelbeek; P. Vineis; A. E. Khan; K. M. Ahmed; A. P. Butler (Climatic Change, 2016)

Reconstructing global overturning from meridional density gradients - E. D. Butler; K. I. C. Oliver; J. J.-M. Hirschi; J. V. Mecking (Climate Dynamics, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Isolation and characterization of an interactive culture of two Paenibacillus species with moderately thermophilic desulfurization ability - Jia Wang; Batzaya Davaadelger; Joelle K. Salazar; Robert R. Butler; Jean-François Pombert; John J. Kilbane; Benjamin C. Stark (Biotechnology Letters, 2015)

Mobilization of horizontally acquired island 2 is induced in planta in the phytopathogen P ectobacterium atrosepticum SCRI 1043 and involves the putative relaxase ECA 0613 and quorum sensing - Bhanupratap R. Vanga; Pavithra Ramakrishnan; Ruth C. Butler; Ian K. Toth; Clive W. Ronson; Jeanne M. E. Jacobs; Andrew R. Pitman (Environmental Microbiology, 2015)
Summary Integrative and conjugative elements ( ICEs ) contribute to the rapid evolution of bacterial pathogens via horizontal gene transfer of virulence determinants. ICEs have common mechanisms for transmission, yet the cues triggering this process under natural environmental or physiological conditions are largely unknown. In this study, mobilization of the putative ICE horizontally acquired island 2 ( HAI 2), present in the chromosome of the phytopathogen P ectobacterium atrosepticum SCRI 1043, was examined during infection of the host plant potato. Under these conditions, mobilization of HAI 2 increased markedly compared with in vitro cultures. In planta ‐induced mobilization of HAI 2 was regulated by quorum sensing and involved the putative ICE ‐encoded relaxase ECA 0613. Disruption of ECA 0613 also reduced transcription of genes involved in production of coronafacic acid (Cfa), the major virulence factor harboured on HAI 2, whereas their expression was unaffected in the quorum‐sensing ( expI ) mutant. Thus, suppression of cfa gene expression was not regulated by the mobilization of the ICE per se , but was due directly to inactivation of the relaxase. The identification of genetic factors associated solely with in planta mobilization of an ICE demonstrates that this process is highly adapted to the natural environment of the bacterial host and can influence the expression of virulence determinants.

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Genetic evidence from the spiny lobster fishery supports international cooperation among Central American marine protected areas - Nathan K. Truelove; Sarah Griffiths; Kim Ley-Cooper; James Azueta; Isaias Majil; Stephen J. Box; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Conservation Genetics, 2015)

Porcine reproductive and respiratory syndrome (PRRS): an immune dysregulatory pandemic - J. E. Butler; K. M. Lager; William Golde; Kay S. Faaberg; Marek Sinkora; Crystal Loving; Y. I. Zhang (Immunologic Research, 2014)

Application of stable isotope mixing models for defining trophic biomagnification pathways of mercury and selenium - H. J. Jones; K. M. Swadling; E. C. V. Butler; L. A. Barry; C. K. Macleod (Limnology and Oceanography, 2014)
Trophic models based on nitrogen stable isotope ratios ( δ 15 N) have been shown to predict changes in mercury (Hg) concentrations in fish; however, they are usually applied at the ecosystem scale and are rarely directed at known trophic pathways. We discuss a novel approach in which we combined gut contents analysis and stable isotope analyses ( δ 15 N and δ 13 C) into a Bayesian isotopic mixing model to provide a quantitative estimate of Hg and selenium (Se) biomagnification in an estuarine food web. Estimates of the relationship between total mercury (THg) and methylmercury (MeHg) were significantly improved in mixing model‐adjusted food webs over models that included all known prey sources. Spatial differences in dietary composition and MeHg bioavailability offer strong evidence that local food webs can have a significant effect on the biomagnification of Hg within benthic fish species. While no evidence of Se biomagnification was found, lower Se : Hg ratios at higher trophic levels could be attributed to increasing trophic Hg concentration. Furthermore, stable isotope analysis suggested Hg and Se biotransfer from benthic sources to fish. Overall, the findings highlight that isotope mixing models can be a significant aid in assessments of contaminant biomagnification, particularly when it is important to define food pathways to top predators.

Invertebrate Community Patterns in Seasonal Ponds in Minnesota, USA: Response to Hydrologic and Environmental Variability - Matthew M. Bischof; Mark A. Hanson; Mark R. Fulton; Randy K. Kolka; Stephen D. Sebestyen; Malcolm G. Butler (Wetlands, 2013)

Effect of Potassium and Nitrogen Fertilizer on Switchgrass Productivity and Nutrient Removal Rates under Two Harvest Systems on a Low Potassium Soil - Maru K. Kering; Twain J. Butler; Jon T. Biermacher; Jagadeesh Mosali; John A. Guretzky (BioEnergy Research, 2013)

Sources of Botrytis cinerea inoculum for flower infection in blackcurrants in New Zealand - K. Boyd-Wilson; F. Obanor; R. C. Butler; P. Harris-Virgin; G. I. Langford; J. T. Smith; M. Walter (Australasian Plant Pathology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Metal Accumulation From Dietary Exposure in the Sea Urchin, Strongylocentrotus droebachiensis - Gretchen K. Bielmyer; Tayler A. Jarvis; Benjamin T. Harper; Brittany Butler; Lawrence Rice; Siobhan Ryan; Peter McLoughlin (Archives of Environmental Contamination and Toxicology, 2012)

Biomass Yield and Nutrient Responses of Switchgrass to Phosphorus Application - M. K. Kering; J. T. Biermacher; T. J. Butler; J. Mosali; J. A. Guretzky (BioEnergy Research, 2012)

Biomass Yield and Nutrient Removal Rates of Perennial Grasses under Nitrogen Fertilization - M. K. Kering; T. J. Butler; J. T. Biermacher; J. A. Guretzky (BioEnergy Research, 2012)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Generation of antibody- and B cell-deficient pigs by targeted disruption of the J-region gene segment of the heavy chain locus - M. Mendicino; J. Ramsoondar; C. Phelps; T. Vaught; S. Ball; T. LeRoith; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; et al. (Transgenic Research, 2011)

Targeted disruption of the porcine immunoglobulin kappa light chain locus - J. Ramsoondar; M. Mendicino; C. Phelps; T. Vaught; S. Ball; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; N. Wertz; et al. (Transgenic Research, 2011)

Leptidea sinapis (Wood White butterfly) egg-laying habitat and adult dispersal studies in Herefordshire - S. A. Clarke; D. G. Green; J. Joy; K. Wollen; I. Butler (Journal of Insect Conservation, 2011)

A New Generation Fatty Acid Amide Hydrolase Inhibitor Protects Against Kainate-Induced Excitotoxicity - Vinogran Naidoo; Spyros P. Nikas; David A. Karanian; Jeannie Hwang; Jianhong Zhao; JodiAnne T. Wood; Shakiru O. Alapafuja; Subramanian K. Vadivel; David Butler; Alexandros Makriyannis; Ben A. Bahr (Journal of Molecular Neuroscience, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Wild Turkey (Meleagris gallopavo) association to roads: implications for distance sampling - Devin R. Erxleben; Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Markus J. Peterson; Nova J. Silvy; William P. Kuvlesky; David G. Hewitt; Stephen J. DeMaso; Jason B. Hardin; Megan K. Dominguez-Brazil (European Journal of Wildlife Research, 2011)

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Distributed Water Infrastructure for Sustainable Communities - Christos K. Makropoulos; David Butler (Water Resources Management, 2010)

Patterns of Tamarix water use during a record drought - Jesse B. Nippert; James J. Butler; Gerard J. Kluitenberg; Donald O. Whittemore; Dave Arnold; Scott E. Spal; Joy K. Ward (Oecologia, 2010)

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Use of weighted reference panels based on empirical estimates of ancestry for capturing untyped variation - Matthew R. L. Egyud; Zofia K. Z. Gajdos; Johannah L. Butler; Sam Tischfield; Loic Le Marchand; Laurence N. Kolonel; Christopher A. Haiman; Brian E. Henderson; Joel N. Hirschhorn (Human Genetics, 2009)

Redox-active antioxidant modulation of lipid signaling in vascular endothelial cells: vitamin C induces activation of phospholipase D through phospholipase A2, lipoxygenase, and cyclooxygenase - Emily Steinhour; Shariq I. Sherwani; Jessica N. Mazerik; Valorie Ciapala; Elizabeth O’Connor Butler; Jason P. Cruff; Ulysses Magalang; Sampath Parthasarathy; Chandan K. Sen; Clay B. Marsh; Periannan Kuppusamy; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2008)

Free-range Village Chickens on the Accra Plains, Ghana:Their Husbandry and Productivity - P. A. T. Aboe; K. Boa-Amponsem; S. A. Okantah; E. A. Butler; P. T. Dorward; M. J. Bryant (Tropical Animal Health and Production, 2006)

Color vision of the budgerigar (Melopsittacus undulatus): hue matches, tetrachromacy, and intensity discrimination - Timothy H. Goldsmith; Byron K. Butler (Journal of Comparative Physiology A, 2005)

Changes in the innate immune response of Atlantic salmon, Salmo salar L., exposed to experimental infection with Neoparamoeba sp. - K A Gross; M D Powell; R Butler; R N Morrison; B F Nowak (Journal of Fish Diseases, 2005)
An experiment was conducted to determine the effect of Neoparamoeba sp. infection on the innate immune responses of Atlantic salmon. Atlantic salmon were experimentally infected with Neoparamoeba sp. and serially sampled 0, 1, 4, 6, 8 and 11 days post‐exposure (dpe). Histological analysis of infected fish gill arches identified the presence of characteristic amoebic gill disease lesions as early as 1 dpe with a steady increase in the number of affected gill filaments over time. Immune parameters investigated were anterior kidney phagocyte function (respiratory burst, chemotaxis and phagocytosis) and total plasma protein and lysozyme. In comparison with non‐exposed control fish basal respiratory burst responses were suppressed at 8 and 11 dpe, while phorbol myristate acetate‐stimulated activity was significantly suppressed at 11 dpe. Variable differences in phagocytic activity and phagocytic rate following infection were identified. There was an increase in the chemotactic response of anterior kidney macrophages isolated from exposed fish relative to control fish at 8 dpe. Total protein and lysozyme levels were not affected by Neoparamoeba sp. exposure.

The prevalence of escaped farmed salmon, Salmo salar L., in the River Ewe, western Scotland, with notes on their ages, weights and spawning distribution - J. R. A. BUTLER; P. D. CUNNINGHAM; K. STARR (Fisheries Management and Ecology, 2005)
The prevalence of escaped farmed Atlantic salmon, Salmo salar L., in the River Ewe, western Scotland, was assessed. After the establishment of smolt cages in the catchment and marine cages near the river mouth during 1986–1987, approximately 425 000 parr and smolts, and 122 000 growers have escaped. Between 1987 and 2001, farmed salmon occurred in the rod fishery in 13 of the 15 years, contributing at least 5.8% of the total catch, with a maximum annual frequency of 27.1%. It was estimated that P

Accuracy, efficiency and robustness of four algorithms allowing full sibship reconstruction from DNA marker data - K. Butler; C. Field; C. M. Herbinger; B. R. Smith (Molecular Ecology, 2004)
In the problem of reconstructing full sib pedigrees from DNA marker data, three existing algorithms and one new algorithm are compared in terms of accuracy, efficiency and robustness using real and simulated data sets. An algorithm based on the exclusion principle and another based on a maximization of the Simpson index were very accurate at reconstructing data sets comprising a few large families but had problems with data sets with limited family structure, while a Markov Chain Monte Carlo (MCMC) algorithm based on the maximization of a partition score had the opposite behaviour. An MCMC algorithm based on maximizing the full joint likelihood performed best in small data sets comprising several medium‐sized families but did not work well under most other conditions. It appears that the likelihood surface may be rough and presents challenges for the MCMC algorithm to find the global maximum. This likelihood algorithm also exhibited problems in reconstructing large family groups, due possibly to limits in computational precision. The accuracy of each algorithm improved with an increasing amount of information in the data set, and was very high with eight loci with eight alleles each. All four algorithms were quite robust to deviation from an idealized uniform allelic distribution, to departures from idealized Mendelian inheritance in simulated data sets and to the presence of null alleles. In contrast, none of the algorithms were very robust to the probable presence of error/mutation in the data. Depending upon the type of mutation or errors and the algorithm used, between 70 and 98% of the affected individuals were classified improperly on average.

Atlantic salmon, Salmo salar L., previously infected with Neoparamoeba sp. are not resistant to re‐infection and have suppressed phagocyte function - K A Gross; R N Morrison; R Butler; B F Nowak (Journal of Fish Diseases, 2004)
Previous studies have indicated that Atlantic salmon, Salmo salar L., affected by amoebic gill disease (AGD) are resistant to re‐infection. These observations were based upon a comparison of gross gill lesion abundance between previously infected and naïve control fish. Anecdotal evidence from Atlantic salmon farms in southern Tasmania suggests that previous infection does not protect against AGD as indicated by a lack of temporal change in freshwater bathing intervals. Experiments were conducted to determine if previous infection of Atlantic salmon with Neoparamoeba sp. would provide protection against challenge and elucidate the immunological basis of any protection. Atlantic salmon were infected with Neoparamoeba sp. for 12 days then treated with a 4‐h freshwater bath. Fish were separated into two groups and maintained in either sea water or fresh water for 6 weeks. Fish were then transferred to one tank with a naïve control group and challenged with Neoparamoeba sp. Fish kept in sea water had lower mortality rates compared with first time exposed and freshwater maintained fish, however, these data are believed to be biased by ongoing mortalities during the seawater maintenance phase. Phagocyte function decreased over exposure time and freshwater maintained fish demonstrated an increased ability to mount a specific immune response. These results suggest that under the challenge conditions herein described, antigen exposure via infection does not induce protection to subsequent AGD.

Comparative In Vitro Surveillance of Amoxicillin-Clavulanic Acid and Four Oral Comparators Against 21,232 Clinical Isolates from Europe - D. J. Hoban; S. K. Bouchillon; J. L. Johnson; G. G. Zhanel; D. L. Butler; K. A. Saunders; L. A. Miller; J. A. Poupard (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

The roles of receptor noise and cone oil droplets in the photopic spectral sensitivity of the budgerigar, Melopsittacus undulatus - T. H. Goldsmith; B. K. Butler (Journal of Comparative Physiology A, 2003)

Quality of life and psychosexual adjustment after prophylactic oophorectomy for a family history of ovarian cancer - L. Elit; M.J. Esplen; K. Butler; S. Narod (Familial Cancer, 2001)

The activity of primate ventrolateral thalamic neurones during motor adaptation - Ernest G. Butler; Darren W. Bourke; Malcolm K. Horne (Experimental Brain Research, 2000)

Neuronal activity in the monkey ventrolateral thalamus following perturbations of voluntary wrist movements - E. G. Butler; Michael C. Harvey; David I. Finkelstein; Malcolm K. Horne (Experimental Brain Research, 1998)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

The effect of thyroid hormones on the aerobic development of locomotor and cardiac muscles in the barnacle goose - K. E. Deaton; C. M. Bishop; P. J. Butler (Journal of Comparative Physiology B, 1997)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)